2016
DOI: 10.1371/journal.pone.0162318
|View full text |Cite
|
Sign up to set email alerts
|

SpyTag/SpyCatcher Cyclization Enhances the Thermostability of Firefly Luciferase

Abstract: SpyTag can spontaneously form a covalent isopeptide bond with its protein partner SpyCatcher. Firefly luciferase from Photinus pyralis was cyclized in vivo by fusing SpyCatcher at the N terminus and SpyTag at the C terminus. Circular LUC was more thermostable and alkali-tolerant than the wild type, without compromising the specific activity. Structural analysis indicated that the cyclized LUC increased the thermodynamic stability of the structure and remained more properly folded at high temperatures when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…Indeed, several doubly labeled enzymes have already been described in the literature, including monomers and SC/ST-modied variants that retain their activity aer labeling. [16][17][18] In our case, however, the resulting Gre2p-SC 2 enzyme revealed only poor polymerization with GDH-ST ( Fig. S1 †).…”
Section: Construction and Characterization Of The Enzyme Hydrogelsmentioning
confidence: 53%
“…Indeed, several doubly labeled enzymes have already been described in the literature, including monomers and SC/ST-modied variants that retain their activity aer labeling. [16][17][18] In our case, however, the resulting Gre2p-SC 2 enzyme revealed only poor polymerization with GDH-ST ( Fig. S1 †).…”
Section: Construction and Characterization Of The Enzyme Hydrogelsmentioning
confidence: 53%
“…The optimal temperature and pH for free and immobilized Cel12A‐SC‐His were 50 °C and pH 6.5, respectively, unlike the discovered pH optimum for plant‐derived Cel12A‐His (pH 5.0), but similar to reported Escherichia coli derived Cel12A (pH 6.0) . Recent studies showed, that the SpyTag/SpyCatcher mediated cyclization is a promising strategy to enhance the structural stability and therefore thermotolerance of enzymes like β‐lactamase, luciferase, or lichenase . If these findings are also applicable to T. reesei endoglucanase Cel12A can be taken into consideration for further work.…”
Section: Discussionmentioning
confidence: 79%
“…[73] Recent studies showed, that the SpyTag/SpyCatcher mediated cyclization is a promising strategy to enhance the structural stability and therefore thermotolerance of enzymes like β-lactamase, luciferase, or lichenase. [62,74,75] If these findings are also applicable to T. reesei endoglucanase Cel12A can be taken into consideration for further work. During these studies an increased thermotolerance could be shown for the fusion of Cel12A to SC.…”
Section: Discussionmentioning
confidence: 90%
“…63 Similar effects on resilience were found for SpyRing versions of phytase, 64 xylanase 65 and luciferase. 66 Apart from temperature, increased tolerance to organic solvents and denaturant has been found upon SpyRing cyclisation. 67 Another approach to enhance stability and performance has been to encapsulate enzymes in protein cages.…”
Section: Enzyme Resilience and Assemblymentioning
confidence: 99%